2021
DOI: 10.32872/cpe.4623
|View full text |Cite
|
Sign up to set email alerts
|

From formative research to cultural adaptation of a face-to-face and internet-based cognitive-behavioural intervention for Arabic-speaking refugees in Germany

Abstract: Background This study aims to provide a transparent and replicable documentation approach for the cultural adaptation of a cognitive-behavioural transdiagnostic intervention (Common Elements Treatment Approach, CETA) for Arabic-speaking refugees with common mental disorders in Germany. Method A mixed-methods approach was used, including literature review, interviews, expert decisions and questionnaires, in order to adapt the original CETA as well as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Regarding specific therapeutic elements, all studies conducted a careful analysis of interventions to address the most common symptoms of psychological distress in their respective target populations. As an example, three studies discussed the inclusion or exclusion of problem solving in their respective interventions ( Böttche et al, 2021 , this issue; Kananian et al, 2021 , this issue; Unterhitzenberger et al, 2021 , this issue). This discussion showed that, on the one hand, problem solving seemed to be a helpful intervention to address the refugees’ most pressing concerns, such as asylum status or family reunification.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding specific therapeutic elements, all studies conducted a careful analysis of interventions to address the most common symptoms of psychological distress in their respective target populations. As an example, three studies discussed the inclusion or exclusion of problem solving in their respective interventions ( Böttche et al, 2021 , this issue; Kananian et al, 2021 , this issue; Unterhitzenberger et al, 2021 , this issue). This discussion showed that, on the one hand, problem solving seemed to be a helpful intervention to address the refugees’ most pressing concerns, such as asylum status or family reunification.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, researchers expressed difficulties in making decisions about cultural adaptations based on the evidence they had gathered on their target population. Two studies specifically focused on this decision-making process from formative research to adaptation (i.e., Böttche et al, 2021 , this issue; Lotzin et al, 2021 , this issue). Only one study documented the decision-making process itself, that is, the opinions expressed by the different researchers on the team.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations